Are AZFb deletions always incompatible with sperm production?. (10th April 2017) - Stouffs, K.; Vloeberghs, V.; Gheldof, A.; Tournaye, H.; Seneca, S.
Summary: Deletions on the long arm of the Y chromosome are a well‐known cause of male infertility and it is generally accepted that deletions involving the AZFb region are not compatible with sperm production. Here, we report on two patients for whom basic diagnostic tests showed a deletion of the AZFb region. Unexpectedly, both patients had some residual sperm production. Subsequently, extension and additional analyses of the AZFb region disclosed an aberrant deletion pattern. Therefore, these results emphasize the need for a detailed and powerful analysis of cases where first‐line Yq deletion tests reveal an AZFb deletion. Moreover, our study clearly demonstrated that only a very careful selection of test markers will avoid the pitfall of a 'no further treatment possible' wrongful conclusion.